PENGARUH PEMBELAJARAN DARING TERHADAP PEMBENTUKAN KARAKTER SISWA DI SMP NEGERI 4 TUALANG KABUPATEN SIAK - Saragi, Ernawanti; Gimin, Gimin; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
This research is motivated by online learning and student character building. The formulation of the problem in this study is whether there is an effect of online learning on the character formation of students at SMP Negeri 4 Tualang Siak District. The purpose of this study was to determine whether there is an effect of online learning on the character formation of students at SMP Negeri 4 Tualang Siak District. The benefits of this research are that this research is expected to be used as study material in the world of education, especially those related to the influence of online learning on the formation of student character, especially in the character of student discipline and responsibility. The sample in this study were students at SMP Negeri 4 Tualang Siak District, totaling 68 respondents, determined by proportional random sampling technique. The data collection instruments are observation, questionnaires, and documentation. Processing of data with quantitative analysis using a simple linear regression formula assisted by the SPSS version 16 application by stating the hypothesis; there is an influence between online learning on the character formation of students at SMP Negeri 4 Tualang Siak District. Processing of data with quantitative analysis using a simple linear regression formula assisted by the SPSS version 16 application by stating the hypothesis; there is an influence between online learning on the character formation of students at SMP Negeri 4 Tualang Siak District. Based on the results of research on the effect of online learning on the formation of students' character in SMP Negeri 4 Tualang Siak District, there is a significant influence between online learning on the formation of students' character in SMP Negeri 4 Tualang Siak District by 23.9%.Key Words: Influence, Online Learning, Student Character Forming.